EFFECT OF SUBSTITUTING CASSAVA LEAF FLOUR (Manihot esculenta) IN COMMERCIAL RATIONS ON THE NON-CARCASS WEIGHT PERFORMANCE OF QUAIL - Rifai, Ahmat; Fathan, Suparmin; Gubali, Syukri; Zainudin, Srisukmawati; Sayuti, Muhammad; Dako, Safriyanto (Jambura Journal of Animal Science, 2025)
Abstract: This study aims to evaluate the effect of cassava leaf meal substitution (Manihot esculenta) in feed on the non-carcass performance of quails. The method used was a complete randomized design (RAL) with 5 treatments and 4 replicates, using a total of 140 quails. Feed treatment consists of: P0 (100% commercial feed), P1 (96% commercial feed + 4% cassava leaf meal), P2 (94% commercial feed + 6% cassava leaf meal), P3 (92% commercial feed + 8% cassava leaf meal), and P4 (90% commercial feed + 10% cassava leaf meal). The variables observed in this study include: non-carcass weight, non-carcass percentage, non-carcass weight of the head, neck, blood, legs, and feathers. The data obtained was then analyzed using multi-dimensional fingerprint analysis (ANOVA) at a real level of 5%, if it shows a real difference (P0.05), then it is continued with the Smallest Real Difference (BNT) follow-up test. The results showed that cassava leaf flour had a real effect (P0.05) on non-carcass weight, non-carcass percentage, and head and neck weight, but had no real effect (P0.05) on blood, legs, and feather weight. Further tests showed that in non-carcass weights, the control treatment (P0) was markedly different from all other treatments (P1, P2, P3, P4), and P1 was markedly different from P3 and P4, while P2 was not markedly different from P3 and P4. In non-carcass percentages, P1 differs markedly from P2, P3, and P4, but does not differ from P0, whereas P0 differs markedly from P2, P3, and P4. In head weights, P1 and P0 were markedly different, while in neck weights, P0 was markedly different from all other treatments. It can be concluded that cassava leaf flour can be used as a substitute in quail feed to improve non-carcass performance, especially in the treatment of 96% commercial feed + 4% cassava leaf flour.